Pencegahan Perundungan (Bullying) Pada Anak di Lingkungan Sekolah - Thresia H.M.Y. Krey; Johan Rongalaha; Winna A.A. Senandi (JURNAL PENGABDIAN PAPUA, 2025)
Bullying is unpleasant behavior whether verbal, physical or social, whether it occurs in cyberspace or in everyday social environments. Bullying can occur at work, at school or on campus and among friends. The consequences of this bullying are that the victim will feel insecure and uncomfortable, feel hurt and depressed. Usually bullying is carried out by individuals or in groups. Perpetrators carry out bullying to hurt other people physically or emotionally, and find a sense of satisfaction when they have bullied their victims Meanwhile, victims of bullying are generally those who look weak and different from their environment, for example physical differences such as skin color, hair shape, body size, and also non-physical differences such as the way a person dresses, the way they speak. Bullying can happen to anyone, and without us realizing it, even school environments that are considered safe are places where bullying occurs most often. Legal education on "Prevention of Bullying of Children in the School Environment" is held in several schools in Jayapura City. This education is carried out to provide an overview and understanding of how we can prevent bullying behavior in the school environment. This legal education is carried out with the aim of knowing the meaning of bullying, the forms of bullying and also to find out the criminal sanctions that can be given to perpetrators of bullying.We hope this activity can provide benefits for students or teenagers as an effort to prevent bullying behavior in the school environment and can become a reference for similar outreach in the future.